Transformational leadership and optimal functioning at work: On the mediating role of employees' perceived job characteristics and motivation - Fernet, C.; Trépanier, S.; Austin, S.; Gagné, Marylène; Forest, J. (Taylor and Francis Ltd, 2015)
This study aimed to deepen our understanding of the motivational mechanisms involved in the relationship between transformational leadership (TFL) and employee functioning. Drawing on the TFL literature, the job demands–resources model and self-determination theory, we propose an integrative model that relates TFL to employee psychological health (burnout and psychological distress), attitudes (occupational commitment and turnover intention) and performance (professional efficacy, self-reported individual and objective organizational performance) through two explanatory mechanisms: perceived job characteristics (job demands and resources) and employee motivation (autonomous and controlled). This research was conducted in two occupational settings (nurses and school principals), using a distinct variable operationalization for each. Results of both studies provide support for the hypothesized model, suggesting that TFL relates to optimal job functioning (psychological health, job attitudes and performance) by contributing to favourable perceptions of job characteristics (more resources and less demands) and high-quality work motivation (more autonomous motivation and less controlled motivation) in employees. Theoretical contributions and managerial implications as well as directions for future research are presented.